The effect of physical activity and body image on the sustainable diets adoption: a comparison between the Italian and Brazilian populations - Borgheresi, Riccardo (2020)
As society amplifies the discussions and practices on sustainability, the concept of sustainable diets is reaching a broader audience. To accelerate dietary behavioural changes towards more sustainable dietary patterns, it is necessary to have a more comprehensive view of consumers’ mental paths. Individuals’ conditions, as the engagement in physical activity and the concern with the one’s body image, might be determinants of healthier and more sustainable choices. The purpose of the present research is to investigate the effects of physical activity and body image on the adoption of a sustainable diet, along with the effect of the perceived benefits of adopting a sustainable diet in moderating these relationships. Using an online consumer-based platform, a survey collected responses of 403 individuals, 202 Italians and 201 Brazilians. The results show that both populations present low levels of physical activity and a mild concern with body image. Respondents have a high perception of the benefits related to sustainable food practices, especially the ones related to their personal sphere. Being engaged in physical activities has proved to positively influence the adoption of sustainable dietary behaviours, while having a concern with body image does not translate into similar results. When investigating the moderating effect of the perceived benefits on physical activity and body image, no effects were confirmed for the adoption of sustainable diets. Italian respondents present lower engagement in physical activity and lower body image concerns than Brazilians, but higher adoption levels overall. These findings expand the marketing and sustainability literature providing emerging consumers’ patterns, and provide important indications for public health and health promotion. A coordinated action of public bodies, health and environmental organizations, and businesses is necessary to guide the transition of individuals towards a healthier lifestyle driven by a more sustainable consumption. The promotion of educational programs, especially directed to young people through the development of awareness-raising campaigns, must focus on sustainable diets as a win-win solution for the environment and the consumers.